2003
DOI: 10.1046/j.1365-2656.2003.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying disease reservoirs in complex systems: mountain hares as reservoirs of ticks and louping‐ill virus, pathogens of red grouse

Abstract: Summary 1.We examined the role of mountain hares in the louping-ill virus/ Ixodes ricinus tick system to determine whether hares were reservoirs of these pathogens for red grouse. A field experiment, which involved reducing mountain hare densities was undertaken and changes in tick abundance, louping-ill virus seroprevalence and red grouse densities recorded. 2.Hares were found to be important hosts for all stages of ticks at two study sites and, where sheep were frequently treated with acaricide, hares fed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 28 publications
2
108
2
1
Order By: Relevance
“…Wader chicks may be at low risk of exposure to both methods of transmission by foraging in habitats which have low tick abundance. In this study, louping ill virus antibodies were found in only 4% of young Red Grouse tested in 2004, which is much lower than those in other areas, for example in Morayshire, where 80% of Red Grouse tested positive for louping ill in 1993 (Laurenson et al 2003). Although 76 wader chicks were tested for louping ill, the low levels found in grouse on these sites mean that larger samples are required before we can conclude that waders do not suffer from the disease.…”
contrasting
confidence: 61%
“…Wader chicks may be at low risk of exposure to both methods of transmission by foraging in habitats which have low tick abundance. In this study, louping ill virus antibodies were found in only 4% of young Red Grouse tested in 2004, which is much lower than those in other areas, for example in Morayshire, where 80% of Red Grouse tested positive for louping ill in 1993 (Laurenson et al 2003). Although 76 wader chicks were tested for louping ill, the low levels found in grouse on these sites mean that larger samples are required before we can conclude that waders do not suffer from the disease.…”
contrasting
confidence: 61%
“…However, here we do not include mountain hares because most areas investing heavily in tick control methods to improve grouse hunting are likely to be maintaining hare numbers at low levels (see Laurenson et al 2003). Model parameter values are given in Table 1 and more detailed justifications are given by Gilbert et al (2001).…”
Section: The Modelmentioning
confidence: 99%
“…However, in some areas where commercial grouse hunting is deemed to be severely limited by LIV, the land managers are highly likely to be already removing sheep from the LIV transmission cycle by either removing them from the area or applying acaricides and vaccinating them against LIV (see Laurenson et al 2003;. It is also likely that land managers will be already maintaining mountain hares at low densities (e.g.…”
Section: Model Limitationsmentioning
confidence: 99%
“…In the Scottish uplands, the complexity of the system is illustrated by the wide range of tick hosts including sheep (Ovis aries L), red deer (Cervus elaphus L), mountain hare (Lepus timidus L) and red grouse (Lagopus lagopus scoticus L) (Gray et al 1992;Hudson et al 1997;Hudson et al 2001;Laurenson et al 2003). Of particular interest is the impact that the sheep tick may have on red grouse, an economically important gamebird, which has been in long term decline (Shaw et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mountain hares have also been implicated in the persistence of LIV through non-viraemic transmission between cofeeding ticks . Experimental reductions of hares have led to declines in tick abundance and LIV with corresponding increases in grouse populations (Laurenson et al 2003) but only where sheep are well managed and red deer are absent. When deer are present, models predict that hare culls are unlikely to be effective because LIV will persist due to the combined effect of deer amplifying the tick population and grouse transmitting the virus (Gilbert et al 2001;Harrison et al 2010).…”
Section: Introductionmentioning
confidence: 99%